A TRANSIÇÃO DE CONTRIBUIDOR INDIVIDUAL PARA LÍDER: A EXPERIÊNCIA VIVIDA PELO PROFESSOR UNIVERSITÁRIO - Fabiula Meneguete Vides da Silva (Universidade Federal de Santa Catarina, 2012)
This study aims to understand the process of transition from individual contributor (teacher) to lead (dean) in universities. The phenomenological-hermeneutic approach of van Manen (1990) was used to recapture the main themes of this experience. Six former university administrators lent their experiences at universities belonging to the Santa Catarina Association of Educational Foundations (ACAFE), through interviews in three stages suggested by Seidman (1998), conducted between May 2009 and March 2010. Drawing on interviews transcribed, it was possible to rescue nine major central themes that represent the experiences that teachers interviewed lived: the structure of universities: one of the challenges; the agenda of the university leader; interpersonal relationships: the diversity in relationships; lack research and the classroom; changing the look: the need for clear focus; seeking professional qualification: "a watershed"; the time: "my number one enemy"; the work environment; and suffering. Data reveal themes useful for understanding the lived experience of teachers in the transition to university leaders, contributing to think about human resources policies in order to minimize the negative aspects experienced by teachers, but also to broaden the research that take into account the theme of transition in the universities.